Ψ-Exponential Stability of Nonlinear Impulsive Dynamic Equations on Time Scales. (10th April 2013) - Hatipoğlu, Veysel Fuat; Uçar, Deniz; Koçak, Zeynep Fidan
Abstract : The purpose of this paper is to present the sufficient ψ -exponential, uniform exponential, and global exponential stability conditions for nonlinear impulsive dynamic systems on time scales.